Penile modification in young Thai men: risk environments, procedures and widespread implications for HIV and sexually transmitted infections. Issue 3 (11th January 2008) - Thomson, N; Sutcliffe, C G; Sirirojn, B; Sintupat, K; Aramrattana, A; Samuels, A; Celentano, D D
Abstract : Objectives: To determine the prevalence and types of penile modification and describe the circumstances surrounding this practice among a sample of young methamphetamine users in Thailand. Methods: A mixed methods study was conducted in Chiang Mai, Thailand, in 2005–6. One hundred young men were surveyed for the quantitative study and in-depth interviews were administered to 9 men, 11 women and 1 transgender. Results: The prevalence of penile modification was 51%, with the most common type being inlaying with muk(s) (61%). The majority of modifications were performed in prison or juvenile detention (80%) by a friend (90%). Motivations for penile modification included peer pressure and perceived enhanced female sexual pleasure. In prison, the practice was veiled in secrecy, the conditions under which modification was performed were unhygienic, sometimes leading to infection, and sharing equipment was common. Men and women reported that condom use was more difficult post modification as condoms were more likely to break or leak and less likely to fit correctly. In addition, sexual intercourse was often painful for the female partner. Conclusion: Penile modification is prevalent in this group of young methamphetamine users and is associated with behaviours and consequences that could facilitate the spread of HIV and other sexually transmitted infections.